2009
DOI: 10.1055/s-0029-1214379
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Fatigue after Resistance Training

Abstract: This study examined the effects of heavy resistance training on dynamic exercise-induced fatigue task (5 x 10RM leg-press) after two loading protocols with the same relative intensity (%) (5 x 10RM(Rel)) and the same absolute load (kg) (5 x 10RM(Abs)) as in pretraining in men (n=12). Maximal strength and muscle power, surface EMG changes [amplitude and spectral indices of muscle fatigue], and metabolic responses (i.e.blood lactate and ammonia concentrations) were measured before and after exercise. After train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
54
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 35 publications
12
54
0
3
Order By: Relevance
“…after S) was significantly larger post-training compared to the corresponding change observed before the training intervention. Although not reflected in blood lactate concentrations, these results indicate an improved fatigue-resistance as previously shown in acute responses to strength loadings after periods of heavy resistance training only (Izquierdo et al 2009(Izquierdo et al , 2011Walker et al 2010). As increased fatigue-resistance allows subjects to sustain a larger magnitude of both mechanical and metabolic stress, the present findings would suggest strength loadings performed immediately before endurance cycling to be more favourable over the reverse loading order.…”
Section: Discussionsupporting
confidence: 69%
“…after S) was significantly larger post-training compared to the corresponding change observed before the training intervention. Although not reflected in blood lactate concentrations, these results indicate an improved fatigue-resistance as previously shown in acute responses to strength loadings after periods of heavy resistance training only (Izquierdo et al 2009(Izquierdo et al , 2011Walker et al 2010). As increased fatigue-resistance allows subjects to sustain a larger magnitude of both mechanical and metabolic stress, the present findings would suggest strength loadings performed immediately before endurance cycling to be more favourable over the reverse loading order.…”
Section: Discussionsupporting
confidence: 69%
“…Similar loads have been shown to maximise power in traditional resistance exercises such as the squat (34) and bench press (10,19,28). Other studies have reported that power in the squat is maximised with slightly heavier loads of 50 to 60% 1RM (28,29).…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies that have measured power during the deadlift have been restricted to maximum loads only. In contrast, research has shown for multi-joint resistance exercises that power is maximized when lifting loads of 30 to 60% 1RM (10,19,28,34). As the deadlift enables large forces to be developed and power is the product of force and velocity, it is possible that submaximal loads similar to those used in previous studies can produce large power outputs.…”
Section: Introductionmentioning
confidence: 88%
“…This drop in the mechanical Control of resistance training by perceived exertion and the EMG signal 4 4 performance would be attributable to a selective fatigue of fast motor units along with a progressive activation of the slow motor unit (8). Additionally some linear models have successfully correlated changes in EMG signal and power loss to assess acute changes in the capability to apply force during resistance exercises (20,21). To the best of the authors' knowledge the sensitivity of both the perceived exertion and the electromyographic signal to differentiate specific moments within the set where the movement velocity peaks, drops below 10% from the maximum, or where the set approaches muscular failure still needs to be properly investigated.…”
Section: Introductionmentioning
confidence: 99%